2013
DOI: 10.1016/j.ijcard.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endothelin receptor antagonism attenuates coronary plaque progression in patients with early atherosclerosis

Abstract: Aim The purpose of the current study was to determine if long term treatment with an endothelin-A (ETA) receptor antagonist attenuates the progression of coronary plaques in patients with coronary endothelial dysfunction. Methods Thirty-five patients with non-obstructive coronary disease and coronary endothelial dysfunction were randomized in a double blind manner to treatment with placebo or ETA receptor antagonist Atrasentan (10 mg) for six months. Endothelial function was assessed by the change in coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 34 publications
0
44
0
1
Order By: Relevance
“…ET-1 antagonists have been shown to decrease the size of atheroma in humans (Yoon et al, 2013). In a mouse model of endothelial ET-1 overexpression (eET-1), we showed that ET-1 is associated with vascular injury characterized by enhanced vascular remodeling, an increase in the formation of reactive oxygen species, and inflammation (Amiri et al, 2004(Amiri et al, , 2008.…”
Section: /2mentioning
confidence: 84%
“…ET-1 antagonists have been shown to decrease the size of atheroma in humans (Yoon et al, 2013). In a mouse model of endothelial ET-1 overexpression (eET-1), we showed that ET-1 is associated with vascular injury characterized by enhanced vascular remodeling, an increase in the formation of reactive oxygen species, and inflammation (Amiri et al, 2004(Amiri et al, , 2008.…”
Section: /2mentioning
confidence: 84%
“…A randomized study of endothelin-A receptor antagonist was reported recently by Yoon et al 41 In addition to its vasoconstrictive properties, endothelin has mitogenic properties, and plays an important role in the development of endothelial dysfunction and progression of atherosclerosis. 42 Plaque volume change was evaluated by intravascular ultrasound in patients with nonobstructive coronary artery disease (CAD) at baseline and 6-month follow-up, and in the coronary artery segments with endothelial dysfunction, significant plaque progression had occurred at the 6-month follow-up, but not in segments with normal endothelial function.…”
Section: Plaque Progressionmentioning
confidence: 99%
“…Recent genome‐wide association studies have implicated the ET A receptor as a genetic determinant of coronary artery disease,54, 55 carotid atherosclerosis,54 large‐artery stroke,55 and peripheral artery disease,56 suggesting a role of this receptor in atherogenesis across diverse arterial systems. These findings are supported by clinical and preclinical studies that suggest a direct role of the ET A receptor on the development of atherosclerosis 57, 58, 59, 60, 61. Recently, Gupta and colleagues demonstrated in a separate genome‐wide association study project that a single‐nucleotide polymorphism common in 5 vascular diseases, including coronary artery disease, promotes exaggerated endothelium‐derived ET‐1 and higher plasma ET‐1 62.…”
Section: Discussionmentioning
confidence: 83%